Influence of PBL parameterization schemes in WRF_ARW model on short - range precipitation's forecasts in the complex orography of Peruvian Central Andes - Moya-Alvarez, Aldo S. (2020)
The study evaluated the sensitivity of the precipitation forecast in the central Andes of Peru of Weather Research and Forecasting (WRF) model to change the planetary boundary layer (PBL) schemes. In that region is located the Mantaro basin, which is one of the most important in the region. Here, the rainfall is very important to the agriculture and to the reserves of drinking water. The simulations were carried out with ten PBL schemes for 19 days in January, February, and March, between 2009 and 2012. Based on the statistical analysis (model vs. observation), the more efficient schemes were determined and analyses of the vertical profiles of some variables are shown. As a result, the schemes that most helped the model in rainfall forecasting were MYNN3 (general and north sector of the basin), Bou-Lac (central sector) and Bretherton-Park (southern sector). The model generally overestimated rainfall in the northern basin, underestimated in the center, and in the south some schemes overestimated and others underestimated. In addition, it was concluded that the boundary layer is more stable in the model than in the observations. The schemes that generated the most rainfall were those that generated a more unstable boundary layer with weaker wind speeds, at least with easterly winds. Another conclusion is that the height of the boundary layer for rainy days in the region at 18 UTC oscillates around 1000 m and that, generally, the wind's velocity changes very little or decreases within the boundary layer and increases above it.